PECULIARITIES OF THE CLINICAL COURSE OF INFLUENZA-ASSOCIATED PNEUMONIA - Bodnar, V.A.; Prymenko, N.O.; Dubynska, G.M.; Котелевська, Т.М.; Bodnar, L.A. (World of Medicine and Biology, 2018)
Influenza is the most common and mass infectious disease on the globe. Thus, according to estimates, annually from 4 to 15% of the world’s population are infected with influenza and acute respiratory diseases, and 250-450 thousand people die of influenza and its complications. Incidence of disease increases to 50-70% of the population during the influenza pandemics, which in the human population are associated with shifted changes in the pathogen. At the same time, the mortality from the flu and its complications ranks first among all infectious diseases. The purpose of the study is to analyze the prevalence and characterize the clinical course of pneumonia as a complication of influenza in the Poltava region. We analyzed the data of the official reporting documentation provided by the State Institution "Poltava Regional Laboratory Center of the Ministry of Health of Ukraine" and the chart of patients with a laboratory confirmed diagnosis of influenza who were in inpatient treatment at the Poltava Regional Clinical Infectious Hospital (PRCIH) in 2016-2017 It was found that in 2017, compared to 2016, in the Poltava region there were 6 times fewer cases of influenza, as indirectly indicated by the number of hospitalized patients due to this pathology in PRCIH. But despite this, the incidence of pneumonia, which complicated the course of influenza according to the data of PRCIH, remained at a consistently high level (20.84% in 2016 and 20.19% in 2017). It was demonstrated that the clinical course of pneumonia as a complication of influenza had some peculiarities. These peculiarities were observed as early as in the initial period of the disease with a predominance of the symptoms of toxic syndrome. This can mask the symptoms of early development of pneumonia and cause hospitalization of patients at a later date. Substantially half of patients had a bilateral inflammatory process, wherein physical changes (auscultatory pattern of pneumonia and a decrease in pulse oxygen saturation) preceded the radiological changes. The course of pneumonia in a significant number of patients was severe with the need for oxygen therapy. Sputum culture in patients with a pneumonia as a complication of influenza more often demonstrated the pathogens such as Stretococcus pneumonia and Staphylococcus aureus.